Burrowing behaviour of the juvenile rapa whelk Rapana venosa (Valenciennes, 1846) reared under laboratory conditions: A protective behaviour. (21st February 2021) - Yu, Zheng‐Lin; Feng, Jie; Song, Hao; Yang, Mei‐Jie; Hu, Zhi; Zhou, Cong; Shi, Pu; Wang, Xiao‐Lin; Zhang, Tao
Abstract: Juvenile Rapana venosa are vulnerable immediately after metamorphosis. The high mortality rate of juveniles seriously limits the development of the aquaculture industry. A number of gastropods use burrowing as an environmental adaptation. R. venosa is a widespread gastropod species, but little is known about its ecology, especially its burrowing behaviour. Here, we studied the obvious burrowing behaviour of juvenile R. venosa . Our results showed that the size of the juvenile snail, grain size of the sediment, dissolved oxygen and water temperature significantly affect the burrowing behaviour of juveniles. Large juveniles have a strong burrowing capacity. The shortest burrowing time occurred in sediment of small grain size. When dissolved oxygen was high (8 mg/L), juveniles displayed obvious burrowing behaviour, and as the dissolved oxygen decreased, the juveniles reduced their burrowing behaviour. Low or high temperatures (≤15 or 30°C, respectively) significantly increased the burrowing rate and depth. Moreover, small snails (shell height <2.5 cm) exhibited obvious shell and tissue detachment (an abnormal phenomenon) when the water temperature was low (5°C). Small snails could reduce shell and tissue detachment and mortality rate by submerging themselves in sand (diameter: 0.50–1.00 mm), indicating that burrowing was a kind of protective behaviour that enables juvenile R. venosa to adapt to the environment. Our results add to the body of knowledge on snail responses to particular environmental factors and allow a better understanding of the species' needs in its natural environment and can be used to improve commercial breeding strategies for R. venosa .